Assessment of internet gaming disorder in clinical research: Past and present perspectives. (June 2014) - Pontes, Halley M.; Griffiths, Mark D.
Abstract Internet Gaming Disorder (IGD) has recently received nomenclatural recognition from official medical bodies as a potential mental health disorder, despite evident variability and inconsistencies in its core conceptualization and psychometric assessment. Research on gaming addiction dates back to the 1970s, and important changes in the field have occurred, especially in terms of definition and conceptualization of the phenomenon, which resulted in a multiplicity of strategies in the assessment of IGD via inconsistent criteria or psychometric tools. In the present review, the authors argue how the adoption of inconsistent criteria and psychometric tools for assessing IGD has negatively influenced the field. Furthermore, this review provides an overview of how the field evolved in terms of its historical developments, current definitions and frameworks, developments in the neurobiological research, psychometric assessment, and emerging trends in the assessment of gaming addiction. Finally, the paper provides information on alternative emerging methods for assessing IGD via sound psychometric tools based on updated and officially recognized conceptualization of the phenomenon of IGD.